2-Additive Multilinear Target-Oriented Preference Functions for Target Setting of Design Requirements - Zhang, Xinwei; Feng, Qiong; Li, Yihang; Eres, Hakki (IEEE transactions on engineering management, 2024)
Setting targets for design requirements (DRs) is critically important to the success of new product development. In the context of quality function deployment (QFD), the customer satisfaction (CS) function for target setting is often modeled by the additive form of DRs, which ignores or cannot fully account for the effects of positive and negative interactions among DRs on CS. Furthermore, uncertain performance levels of competitors' products have not been explicitly integrated into the CS function. Therefore, the CS function cannot fully consider the competitiveness of targets. Aiming to solve these two issues, 2-additive multilinear target-oriented preference functions (MTPFs) are proposed in this article to build nonadditive objective functions of CS for target setting. First, the equivalence between 2-additive MTPFs and 2-additive multilinear models based on fuzzy measures is established, enabling identifying the coefficients of 2-additive MTPFs based on fuzzy measures. Second, a five-step procedure is proposed to build 2-additive MTPFs for target setting. This proposed approach has the advantages of dealing with 2-additive interactions among pairs of DRs explicitly in the objective function and integrating the probability of achieving competitors' performance levels into the CS function. It can be conveniently integrated into a QFD model considering pairs of correlations among DRs and characteristics of technical competitive analysis. To demonstrate the feasibility and effectiveness of the proposed approach, it is applied to an example of target setting for portable electrocardiogram device development.